2017
DOI: 10.1002/cncr.30692
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative chemotherapy versus postoperative chemoradiotherapy in patients with resectable gastric/gastroesophageal junction adenocarcinomas: A survival analysis of 5058 patients

Abstract: In this large series of patients with stage II/III resected gastric/GEJ adenocarcinomas from >1500 American College of Surgeons Commission on Cancer-accredited facilities, patients receiving PECT were shown to survive longer than those receiving POCRT. Cancer 2017;123:2909-17. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…An analysis of >5000 patients with esophageal and GEJ adenocarcinomas diagnosed between 2004 and 2013 demonstrated a substantially decreased risk of death with the receipt of POC over postoperative chemoradiation (adjusted HR, 0.58; P < .001). 20 Others have found no survival gain with the addition of preoperative RT to neoadjuvant chemotherapy and surgery (HR, 1.08; P = .23). 21 Last, Mokdad et al reported on >10,000 patients in the NCDB with locally advanced esophageal and GEJ adenocarcinomas who were treated with preoperative chemoradiation, and reported a significant benefit to the addition of adjuvant chemotherapy (HR, 0.79; P < .001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An analysis of >5000 patients with esophageal and GEJ adenocarcinomas diagnosed between 2004 and 2013 demonstrated a substantially decreased risk of death with the receipt of POC over postoperative chemoradiation (adjusted HR, 0.58; P < .001). 20 Others have found no survival gain with the addition of preoperative RT to neoadjuvant chemotherapy and surgery (HR, 1.08; P = .23). 21 Last, Mokdad et al reported on >10,000 patients in the NCDB with locally advanced esophageal and GEJ adenocarcinomas who were treated with preoperative chemoradiation, and reported a significant benefit to the addition of adjuvant chemotherapy (HR, 0.79; P < .001).…”
Section: Discussionmentioning
confidence: 97%
“…The value of RT in addition to surgery with or without chemotherapy has been unclear when explored using other large data sets. An analysis of >5000 patients with esophageal and GEJ adenocarcinomas diagnosed between 2004 and 2013 demonstrated a substantially decreased risk of death with the receipt of POC over postoperative chemoradiation (adjusted HR, 0.58; P < .001) . Others have found no survival gain with the addition of preoperative RT to neoadjuvant chemotherapy and surgery (HR, 1.08; P = .23) .…”
Section: Discussionmentioning
confidence: 99%
“…However, such patient selection is unlikely to account for the difference in conclusions between that study and the current one, as institution was not a prognostic factor even when patients receiving preoperative chemotherapy were eliminated from the analysis. Furthermore, preoperative chemotherapy has been associated with enhanced survival compared with postoperative chemotherapy, 18 The current study has several limitations. This is a retrospective study comparing data from two different institutions in disparate regions of the world, so the analysis is vulnerable to both confounding factors and selection bias despite our best efforts to adjust for differences between the two groups.…”
Section: Discussionmentioning
confidence: 87%
“…One study demonstrated a survival advantage for perioperative chemotherapy, especially in patients who were down-staged from lymph node-positive to lymph node-negative disease after neoadjuvant chemotherapy. 12 Another study found an improved overall survival with adjuvant chemoradiation, particularly in patients with margin positive resections. 13 Another study using a California cancer registry found similar outcomes between perioperative chemotherapy and adjuvant chemoradiation for clinically node-positive patients, though chemoradiation resulted in better survival for node-negative patients or those with signet ring cell histology.…”
Section: Discussionmentioning
confidence: 99%